Youth duo against graying In Al-Bakhri's Poetry: An Analytical Study - Ali, Waleed Owaid Hussein; Al-Shuwaili, Arkan Hussein Muttar (Al-Adab Journal, 2021)
Anti-binaries are among the topics that raised the efforts of researchers and scholars in Arab literature, both ancient and modern, and took a literary and critical dimension alike, because of their philosophical value, in which poets' ingenuity and the value of their literary product are shown, and it is in this spirit that we deliberated in this research on monitoring the youth / gray dualism In the poetry of Ali Bin Al-Hassan Al-Bakhrazi and how he managed to employ this dichotomy with unique poetic versatility and high stylistic sobriety, and we worked to bring out the most clear texts in a poetry and the most brilliant in its meanings, as the poet has a high poetic, suggestive language and a tyrannical symbolism, and the topic of youth / gray poetry in his poems is from Ok T diodes presence and manifestation, and most simulation of the reality of social life and psychological .